Exploring Perceptions and Utilization of Biometric Technologies from Consumer Perspective - Hustava Sipulova, Marta; Taborecka, Janka; Valova, Henrieta (International Review of Management and Marketing, 2025)
In recent decades, the use of information and communication technologies has become widespread among users. The use of biometric technologies brings benefits, such as fast login, increased security, convenience, and fraud prevention. However, for the successful adoption of this technology by users it is essential to examine their attitudes, opinions, preferences, habits, experiences, and other aspects. In Slovakia and CEE region, there is still a lack of studies that examines consumers’ perspectives on the use of biometric technologies. Our paper presents partial results of a broader research project focused on the awareness, willingness and real use of biometric technologies by Slovak consumers. Data was collected by a questionnaire survey on a sample of n = 615 respondents, representative by gender and age. Using the Friedman test, we found differences in respondents’ willingness, awareness, and use of biometric technologies. The most well-known biometric methods identified and used included fingerprints, facial biometrics, or signatures. Consumers were mostly willing to use biometric technologies to unlock personal devices, use them in healthcare, transportation, or at the workplace. Respondents are least likely to use them for marketing purposes, which is interesting given the growing potential of this area, especially in the retail sector. This could pose a challenge for businesses to overcome this barrier. Appropriate communication about the benefits and risks is important to increase trust and acceptance of biometric technologies.